Isolation of Na-alginate from Brown Seaweed (Padina sp.) and Synthesis of Na-alginate-chitosan Polyelectrolytecomplex (PEC) Film as Methylene Blue Adsorbent - Rahayu, Rahayu; Bandjar, Adriani; Nurlete, Samsul; Sohilait, Mario Rowan; Baunsele, Anselmus Boy (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
Na-alginate has been isolated from brown seaweed (Padina sp.) and then used to make na-alginate-chitosan complex polyelectrolyte films as methylene blue adsorbent. Characteristics of na-alginate, chitosan, and PEC films before and after adsorption were carried out using an FT-IR spectrophotometer. Na-alginate-chitosan PEC film was made by mixing a 0.3% (w/v) Na-alginate solution with a 1% (w/v) chitosan solution with a chitosan-alginate volume ratio (1:3). The film formed was tested for its resistance in pH 3-11 for 7 days and showed that the film could survive in acidic or alkaline media. The adsorption study carried out resulted in maximum concentration data occurring at 75 mg/L with a capacity of 30.2768 mg/g.